PENERAPAN ERM PADA LEMBAGA FINTECH (STUDI KASUS DI PT INVESTREE RADHIKA JAYA) - Erna Sari Putri; Rekliary Maylafaza Rachmaniar; Elsi Mersilia Hanesti (LPPM STIE PERTIBA Pangkalpinang, 2023)
All companies require risk management to mitigate risks in their respective companies. Starting from conventional financial institutions to even Fintech, they must implement a good risk management system for company operations. Enterprise Risk Management (ERM) is a comprehensive approach that can be used as an effective method by companies to manage existing risks. Fintech is a startup company that provides technology-based financial services in the form of a platform that makes it easy for the public. The research uses the interview method centered on the Risk Management at PT Investree Radhika Jaya. The risk management analysis was carried out using the COSO version of ERM which consists of eight interconnected components and the analysis focuses on default risk. From these eight components, it can be seen how the company's internal environment is, the risks they face, and how they manage these risks. Because PT Investree Radhika Jaya is a startup company that is still new, several regulations and implementation of risk management in the company are still immature and have the possibility to experience changes along with the development of the company.